Head and neck necrotizing fasciitis: the importance of negative pressure wound therapy with literature review - Aljanabi, Kasim S. Kasim (2023)
Necrotizing fasciitis (NF) is highly progressive subcutaneous tissue infection that causes necrosis of the skin and subcutaneous tissue. NF due to streptococci showed an incidence of 2.79/100,000 patient per year, with a slightly higher number of elderly male patients (53%). Skin lesions/wounds were the most common predisposing factor; it was reported in 25% of cases. Skin and soft tissue were the most common foci of infection, with 32% of patients having cellulitis and 8% necrotizing fasciitis (Lamagni et al. 2008). Immune compromised patients are more prone to develop this kind of infection.